Effect of passive modified atmosphere packaging on the quality of minimally processed sibuyas tagalog (Allum cepa L. var. ascalonicum) - Abad, Aissa A.; Rumbaoa, Rowena Grace O. (2009.)
ABSTRACT The influence of different commercially available plastic films on the quality of minimally processed Sibuyas Tagalog onion was assessed in this study. In particular, diced onions (about 1 cm) were dipped in chlorinated water (100 ppm), packed in different plastic films, and stored at 0-7°C for 12 days. Four different packaging materials were used: low density polyethylene (LDPE) bag, polypropylene (PP) bag, polystyrene (PS) clamshell, and expanded polystyrene (EPS) tray overwrapped with polyvinyl chloride (PVC) film. Unpacked samples served as control. Determination of effects on pyruvic acid concentration, microbiological activity and total soluble solid content were determined at days 0, 4, 8, and 12. Weight loss was monitored everyday for 12 days. Results showed significant reduction in weight loss of all samples stored under passive modified atmosphere packaging. Diced onions packed in PP bag did not have significant change in pyruvic acid concentration while diced onions in PE bag, PS clamshell, and EPS-PVC film showed increased pyruvic acid concentration like the unpacked samples. Levels of total soluble solids of samples under MAP did not have significant change during storage. Microbiological development was delayed on all MAP treated samples.
Thesis (B.S. Food Technology)--University of the Philippines Diliman.
Keywords: Onions -- Philippines; Onions -- Packaging